LAJU INTENSITAS SERANGAN JAMUR. PEWARNA PADA KAYU TUSAM (PINUS MERKUSII JUNGH. ET DE VR.) - Dominicus Martono (Jurnal Penelitian Hasil Hutan, 1989)
The intensity of sapstain infestation on tusam logs (Pinus merkusii Jungh. et de Vr.) was studied in a field of Suka- bumi Forest District, West Java. The material used consisted of one meter long fresh logs taken from newly felled trees. The tested logs were tried at the filed for three months using four storage levels.Surface staining and the loss of water content were weekly observed for one .month, while the rate of staining penetration was observed for three months after the treatment.The result showed that the degree of staining defect was significantly defferent within the period of inspection, but that was not among the log sections. The rate of staining penetration is approximately 5 cm per week.